Design and baseline characteristics of participants in the Researching cardiovascular Events with a Weekly INcretin in Diabetes (REWIND) trial on the cardiovascular effects of dulaglutide. Issue 1 (14th July 2017) - Gerstein, Hertzel C.; Colhoun, Helen M.; Dagenais, Gilles R.; Diaz, Rafael; Lakshmanan, Mark; Pais, Prem; Probstfield, Jeffrey; Riddle, Matthew C.; Rydén, Lars; Xavier, Denis; Atisso, Charles M.; Avezum, Alvaro; et al.
Abstract : The aim was to determine the effects of dulaglutide, a synthetic once‐weekly, injectable human glucagon‐like peptide 1 analogue that lowers blood glucose, body weight, appetite and blood pressure, on cardiovascular outcomes. People with type 2 diabetes, aged ≥50 years, with glycated haemoglobin (HbA1c) ≤9.5%, and either a previous cardiovascular event, evidence of cardiovascular disease or ≥2 cardiovascular risk factors were randomly allocated to a weekly subcutaneous injection of either dulaglutide (1.5 mg) or placebo and followed within the ongoing Researching cardiovascular Events with a Weekly INcretin in Diabetes (REWIND) trial every 3 to 6 months. The primary cardiovascular outcome is the first occurrence of the composite of cardiovascular death or non‐fatal myocardial infarction or non‐fatal stroke. Secondary outcomes include each component of the primary composite cardiovascular outcome, a composite clinical microvascular outcome comprising retinal or renal disease, hospitalization for unstable angina, heart failure requiring hospitalization or an urgent heart failure visit, and all‐cause mortality. Follow‐up will continue until the accrual of 1200 confirmed primary outcomes. Recruitment of 9901 participants (mean age 66 years, 46% women) occurred in 370 sites located in 24 countries over a period of 2 years. The mean duration of diabetes was 10 years, mean baseline HbA1c was 7.3%, and 31% had prior cardiovascular disease. The REWIND trial's international scope, high proportion of women, high proportion of people without prior cardiovascular disease and inclusion of participants whose mean baseline HbA1c was 7.3% suggests that its cardiovascular and safety findings will be directly relevant to the typical middle‐aged patient seen in general practice throughout the world. Abstract : A video related to the article is available on the journal's YouTube site:https://www.youtube.com/watch?v=vg_XhSPKxww&feature=youtu.be